Asuhan Keperawatan Pada Ny. K Keluarga Tn. I Dengan Gangguan Sistem Kardiovaskuler: Hipertensi Di Desa Tonjong RT 02 RW 04 Kecamatan Tonjong Kabupaten Brebes - Luviana Nur Maulida Ardati; Tati Karyawati (STIKES Columbia Asia Medan, 2026)
Hypertension is a condition in which systolic blood pressure exceeds 140 mmHg and diastolic blood pressure is above 90 mmHg. Hypertension is the leading chronic non-communicable disease among adults in Indonesia, with a prevalence of 26.5%, and tends to increase with age. Family nursing care plays an important role in helping patients manage hypertension through education, pharmacological and non-pharmacological interventions, and ongoing monitoring. This case study aimed to describe comprehensive nursing care for Ny. K, a 66-year-old patient from the family of Tn. I, diagnosed with hypertension in Desa Tonjong RT 02 RW 04, Kecamatan Tonjong, Kabupaten Brebes. Nursing care was conducted from December 27 to 29, 2025, using interview, physical examination, observation, and documentation methods. Two nursing diagnoses were identified: (1) Risk of ineffective cerebral tissue perfusion, and (2) Knowledge deficit related to hypertension. Nursing interventions included vital sign monitoring, oral medication administration (Amlodipine 10 mg), health education on hypertension, and non-pharmacological therapy using bay leaf (Syzygium polyanthum) decoction. Evaluation results showed that the knowledge deficit was resolved after one session of health education, while the risk of ineffective cerebral tissue perfusion was partially resolved, with blood pressure decreasing from 180/100 mmHg to 165/90 mmHg over three home visits. It is recommended that families continue the bay leaf decoction therapy for one week and maintain regular blood pressure monitoring at the nearest health facility.